Ancillary shrine to the northeast of Neelkanth Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
This is the ancillary shrine to the northeast of the main Neelkanth Mahadev Temple. It is a single-shrine temple in a very dilapidated state. Only a few mouldings of its plinth have survived. The temple was originally pancharatha (five vertical offset or projections on each side) in its plan, but the structure of the mandapa (pillared hall) has fallen.